Peran Guru dan Strategi dalam Meningkatkan Pembelajaran Aktif Siswa di Kelas IV SD Al-Huda Sidoarjo - Sholicha, Nikmatus; El-Yunusi, Muhammad Yusron Maulana (Lembaga Intelektual Muda (LIM) Maluku, 2024)
Active student learning is an approach in which students are actively involved in the learning process, not just as passive recipients of information from the teacher. Active learning involves student participation in learning activities such as discussions, problem solving, experiments, and collaboration, which allows them to construct their own understanding in a deeper and more relevant way. The purpose of this study was to analyze the role and strategies of teachers in improving active learning in grade IV students of Al-Huda Elementary School, Sidoarjo. The research method used was qualitative with data collection techniques through observation, interviews, and literature studies. The data analysis techniques used were data reduction, data presentation, and drawing conclusions. The informants in this study were homeroom teachers of grade IV at Al-Huda Elementary School. The results showed that the role of teachers in improving active learning in the classroom had gone well even though there were some obstacles in its implementation. Through the role and strategies of teachers, it aims to encourage critical thinking, problem solving, and student independence in their learning